ATTRIBUTES OF FORMING OF COMMUNICATIVE CULTURES IN TORONTO - Пахомов, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The attributes of forming of communicative culture in Toronto are traced in the article. It pays attention on powerful «Ukrainian track» in Canada, in particular on the sights of the Ukrainian cultural legacy.